The Life, Diaries and Correspondence of Jane Lady Franklin 1792–1875 - Franklin, Jane 1791-1875 (Cambridge library collection. Polar exploration, 1923)
Jane Franklin (1792–1875) became well known in the middle of the nineteenth century for her tireless campaign to discover the fate of the lost Arctic expedition led by her husband, Sir John Franklin (1786–1847). The editor of this volume, Willingham Franklin Rawnsley (1845–1927), was Sir John's great-nephew, with access to the family papers. The four sections of this work, first published in 1923, address Jane's life before her marriage in 1828; the period when her husband was posted to the Mediterranean; life in Tasmania, where Sir John served as governor; and Lady Franklin's quest to learn the fate of her husband's expedition in search of the North-West Passage. Given appropriate context, the extracts illuminate her interest in European travel, her activities in Tasmania - especially in education and the treatment of female convicts - and her movements over the globe after searches discovered evidence of her husband's demise